From Occupied Voids to Nanoprecipitates: Synthesis of Skutterudite Nanocomposites in situ 1. Issue 8 (25th June 2015) - Eilertsen, James; Surace, Yuri; Balog, Sandor; Sagarna, Leyre; Rogl, Gerda; Horky, Jelena; Trottmann, Matthias; Rogl, Peter; Subramanian, M. A.; Weidenkaff, Anke
Abstract: Nanocomposite thermoelectrics can exhibit both reduced thermal conductivity and enhanced electrical conductivity beyond single‐phase materials; accordingly, they have become the new material paradigm to achieve viable thermoelectric efficiencies. New synthesis techniques are needed to further enhance their properties. A novel technique, designed to synthesize nanoprecipitates within a well‐sintered single‐phase polycrystalline matrix, is reported. The technique, attrition‐enhanced nanocomposite synthesis (AENS), comprises three stages: (1) Synthesis of cage‐like crystal structures with metastable interstitials, followed by (2) severe plastic deformation (SPD), and finally (3) rapid sintering with concomitant interstitial precipitation. The efficacy of this technique is demonstrated in this work. Filled cage‐like skutterudite In0.2 Co4 Sb12 samples are synthesized and spark‐plasma sintered. They are subjected to severe plastic deformation via high‐pressure torsion, and finally sintered again via spark‐plasma sintering in order to precipitate the metastable interstitials. X‐ray diffraction, scanning‐electron microscopy, and small‐angle neutron scattering (SANS) of In0.2 Co4 Sb12 samples subjected to this procedure demonstrate that indium precipitates rapidly, and forms nano‐sized In‐based inclusions. In addition, the amount of precipitated indium, and the size and distribution of the nanoprecipitates are strongly influenced by the extent of plastic deformation. This technique can be employed to synthesize efficient thermoelectrics as well as materials with a number of applications requiring rapid synthesis of nano‐sized precipitates. Abstract :